New religious movements : challenge and response - Wilson, Bryan R.; Cresswell, Jamie (Routledge, 1999)
Focusing on five countries (Italy, Brazil, Germany, Britain and the United States), New Religious Movements offers a comprehensive and wide-ranging study of the phenomena and impact of new religions.